'Feedback: Where data finally get thrilling' - tools for facility managers to use data for improved health outcomes in the prevention of mother-to-child transmission of HIV and antiretroviral therapy - J Murphy; C-H Mershon; H Struthers; J McIntyre (AOSIS, 2013)
Data use and data quality continue to be a challenge for government sector health facilities and districts across South Africa. Led by the National Department of Health, key stakeholders, such as the Anova Health Institute and district health management teams, are aligning efforts to address these gaps. Coverage and correct implementation of existing tools - including TIER.net, routine data collection forms and the South African District Health Information System - must be ensured. This conference report provides an overview of such tools and summarises suggestions for quality improvement, data use and systematic evaluation of data-related interventions.